SrBi2Nb2O9 thin films crystallized using a low power microwave oven - Zanetti, S. M.; Vasconcelos, J. S.; Vasconcelos, NSLS; Leite, E. R.; Longo, Elson [UNESP]; Varela, José Arana [UNESP] (Elsevier B.V., 2004)
SrBi2Nb2O9 thin films were produced by the polymeric precursor method using an aqueous solution. The crystallization of the films was carried out using a domestic microwave oven by means of a SiC susceptor in order to absorb the microwave energy and rapidly transfer the heat to the film. Low microwave power and short time have been used. The films obtained are well-adhered, homogeneous and with good specularity, even when treated at 600 degreesC for 10 min. The microstructure and the structure of the films can be tuned by adjusting the crystallization conditions. Depending on the direction of the heat flux it is possible to obtain preferential oriented or polycrystalline films in the microwave oven for 10 min. The microstructure presented a polycrystalline nature with spheroid small mean grain size when the susceptor is placed above the substrate. When the susceptor is placed below the substrate, the films presented platelet grains with mean grain size around 250 nm and a 001 orientation. For comparison, films were also prepared by the conventional method at 700 degreesC for 2 h. (C) 2003 Elsevier Ltd. All rights reserved.
Keywords: ferroelectric; microwave; SrBi2Nb2O9; thin films